Check My School : A Case Study on Citizens’ Monitoring of the Education Sector in the Philippines - Shkabatur, Jennifer (World Bank, Washington, DC, 2015)
Check My School (CMS) is a community monitoring project that aims to promote transparency and social accountability in the Philippine education sector by tracking the provision of services in public schools. The project uses a blended approach, which combines on-the-ground community monitoring with the use of information and communication technology (ICT). CMS had been initiated and designed by the Affiliated Network for Social Accountability in East Asia and the Pacific (ANSA-EAP) and jointly supported by the World Bank Institute and the Open Society Institute. Although CMS is a young project (the pilot began in early 2011), it has already attracted worldwide attention of governments, civil society organizations, and international donors. CMS is often cited as a ‘good practice’ in the field, and the governments of several countries, including Indonesia, Kenya, and Moldova, are interested in adapting the CMS model to their country contexts. This case study sheds light on the design and implementation features of the first pilot cycle of CMS in public schools across the Philippines. The case study discusses the general political background and operating environment of the CMS project, its concept and operating principles, the roles and incentives of the major stakeholders involved in its design and implementation, and the ways in which CMS aims to use ICTs. In addition, the case study provides a step-by-step analysis of the first CMS project cycle in 2011, examines its accomplishments and challenges, and provides lessons from the first pilot year of the project’s operation. The case study concludes with recommendations for projects that aim to follow the footsteps of CMS.